Understanding the Role of Literature in Shaping Societal Norms: A Comparative Analysis of Contemporary Works - M.Z. , Iqbal Hafiz (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2023)
Literature has long been recognized as a powerful tool for shaping societal norms and values. This study explores the role of literature in shaping societal norms through a comparative analysis of contemporary works. Employing a qualitative approach and drawing on extensive literature reviews and library research, this research delves into the themes, narratives, and characters portrayed in a diverse selection of contemporary literary works from various cultural contexts. By examining how literature reflects and influences societal attitudes towards issues such as gender roles, race relations, and moral values, this study aims to provide insights into the dynamic interplay between literature and social change. Through comparative analysis, this research seeks to identify common patterns, divergent perspectives, and underlying messages embedded within contemporary literary texts.